Optical tactile array sensor for lump detection in soft tissue - Yıldız, Mustafa Zahid. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2007., 2007)
Tactile information has great importance in many areas. Receiving tactile information from a slave-robot is a necessary component of tele-detection with tactile display. Surgeons highly depend on tactile feedback in minimally invasive surgery to locate arteries and tumors hidden in tissue. Additionally physicians use palpation for a variety of medical procedures to find tumors and arteries, as well as to assess the health of soft tissue. For these applications, tactile sensors can provide objective, quantitative, and consistent measurements. The tactile feedback may restore the lost tactile sensation as well. Determining a palpable suspicious abnormality needs continued monitoring and requires maintaining a record of the examination results, but at present verbal notes are used and they are limited to subjective information about the position, size, and hardness of the lump. Because it is difficult to verbalize tactile sensations, tactile sensors should be used for quantitative measurements. In this study, an optical tactile array sensor has been developed. It has advantages over pre-existing discrete tactile sensors in terms of pattern recognition and sensing a pressure distribution over an area. The deformation of elastic silicon-rubber surface was measured optically. It can be used in breast tumor identification which has been conventionally done by hand palpation. The tactile probe can detect lumps in soft tissues and can also draw a map of the sample. This map can be fused on a real picture of the tissue to determine the probable location. The sensor consisted of 5x5 phototransistor array, 4x4 infra-red light sources, and silicon-rubber elastic surface. Each sensor output was selected by using a 16-bit multiplexer and the output signal was detected by a data-acquisition card. The software was developed in MATLAB. The sensor produces an image which shows the contact surface and quantitative and visual results are presented to the user. The sensor has a wide dynamic range (1 to 750 g), and high linearity (R2=0.927). The tactile sensor was tested with two phantoms, 7 different Von Frey Hairs and fingertip contact experiments.
Keywords: Tactile sensors.; Palpation.